Research on optimal configuration of park-level multi-energy complementary system with multiple evaluation indexes - Wu, Yingjun; Chen, Ji; Zhang, Xinyuan; He, Kewei; Jin, Lei (Frontiers in Energy Research, 2023)
At present, energy shortages are becoming increasingly severe, and the concept of park level multi energy complementary systems (MECS) has provided direction for sustainable energy development. In recent years, how to improve the economy and reliability of multi energy complementary systems has become a research hotspot in this field. In this paper, a two-layer optimal scheduling strategy is proposed to allocate the capacity of various energy equipment in the park, considering the comprehensive energy self-sufficiency rate, comprehensive energy utilization rate and energy shortage expectation. The proposed capacity allocation scheme can effectively improve the economy of MECS in the park. Finally, the effectiveness and practicability of the algorithm are verified by simulation analysis.